Sulfate radicals induced from peroxymonosulfate by cobalt manganese oxides (CoxMn3−xO4) for Fenton-Like reaction in water - Yao, Y.; Cai, Y.; Wu, G.; Wei, F.; Li, X.; Chen, H.; Wang, Shaobin (Elsevier, 2015)
A series of CoxMn3−xO4 particles as Fenton-like solid catalysts were synthesized, and their catalytic performance in oxidative degradation of organic dye compounds in water was investigated. The surface morphology and structure of the CoxMn3−xO4 catalysts were characterized by field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM), powder X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). The results showed that, as an oxide composite of Co and Mn elements, CoMn2O4 showed much stronger catalytic activity in peroxymonosulfate (PMS) oxidation than Co3O4, Mn2O3, and their physical mixture. Typically, the uses of 0.02 g/dm3 CoMn2O4 and 0.2 g/dm3 PMS yielded a nearly complete removal of Rhodamine B (0.03 g/dm3) in 80 min at 25 °C. The efficiency of Rhodamine B decomposition increased with increasing temperature (15–55 °C), but decreased with the increase of fulvic acid concentration (0–0.08 g/dm3). Furthermore, CoMn2O4 could maintain its catalytic activity in the repeated batch experiments. Moreover, HOradical dot and SO4radical dot− radicals participating in the process were evidenced using quenching experiments, and a rational mechanism was proposed. PMS oxidation with CoMn2O4 is an efficient technique for remediation of organic contaminants in wastewater.